The Cooperation Council for the Arab States of the Gulf between Regional and International Threats - Altameme, Maha Saad Abdulkareem (Dirasat: Human and Social Sciences, 2025)
Objectives: The research aims to study the sources of threats facing the security of the Gulf Cooperation Council (GCC) countries, ranging from international and regional threats, as well as intra-regional threats arising from differences in views and perceptions regarding the concept of security. Methods: The researcher followed the descriptive analytical approach, organizing the research into three sections: the first to identify regional threats represented by the Iranian threat, the second section addressed the United States and the security of the Gulf Cooperation Council (GCC) countries, while the final section focused on studying the differences in views and perceptions among GCC countries regarding security issues. Results: The study showed that Iran has been and continues to be the biggest threat to the security of the Gulf Cooperation Council (GCC) countries due to its expansionist ambitions in the Arabian Gulf. Differences in threat perceptions among these countries have exacerbated tensions among them, to the extent that Gulf-Gulf disputes have become a source of danger to the security of the Gulf Cooperation Council (GCC) countries, especially following the declining US commitment to their security. Conclusions: The study recommends activating the decisions and laws enacted by the Gulf Cooperation Council (GCC) and unifying their defense and security policies to mitigate the risks surrounding the security of the Gulf Cooperation Council (GCC) countries.